Academic Librarians and Research Data Services: Preparation and Attitudes Revisited. Issue 4 (2nd October 2022) - Rachlin, David J.
Abstract: Carol Tenopir et al. published a landmark study of research data services librarians in 2013. The object of this study is to determine if and how librarians' attitudes about RDS and their perceptions of their own preparedness to provide RDS have changed as the apparent need for and importance of RDS has continued to grow since the publication of Tenopir's research. This research project was completed by surveying academic librarians in ARL libraries. The survey was distributed to the deans & directors of ARL libraries, to be disseminated to the librarians there most directly involved in RDS. After analyzing the data, I was able to determine that there has been a measurable increase in the perceived importance of RDS among librarians working with data. There has also been a significant increase in the proportion of librarians working with RDS who feel that they have the skills and support needed to do their work. It is my conclusion that RDS seems to be gaining traction within academic libraries, but it is unclear if this is due to libraries placing additional importance on these services.